ANALISIS KUALITATIF BAKTERI COLIFORM PADA AIR BAK PENAMPUNGAN UMUM DESA TARAJU KABUPATEN KUNINGAN - Wawang Anwarudin; Didi Suhendi; Nur Azizah (Jurnal Farmaku (Farmasi Muhammadiyah Kuningan), 2019)
Water is a very important material in life so that the quality must meet the requirements as clean water and the requirements for drinking water. This study aims to determine the total value of coliform bacteria in the water of public water reservoirs in the Taraju village of kuningan district. The method used in this study is the description of the observation method, and the total coliform value test in this study using the Most Probable Number (MPN) method series 3-3-3. The water samples used was taken from 4 public water reservoirs in the Taraju village. The results of the study of 4 reservoir water samples showed coliform bacteria in the estimation and confirmation test which was characterized by gas and acid formation, and of all the samples tested showed the value of coliform bacteria ≤50/100 mL. The conclusion is that the water of public water reservoirs in Taraju village contains Coliform bacteria so that it does not meet the quality requirements of drinking water, but qualifies as clean water in accordance with the Minister of Health Regulation No.416/MEN.KES/PER/ IX/1990.